Analysis of the Business Model and Marketing Strategy of Internet Celebrity Tourism Spot: A Case Study of Hongshan Zoo - Gao, Yiqian (Transactions on Social Science, Education and Humanities Research, 2024)
With the recovery of the economy, the cultural tourism market is developing strongly. People's living standards have improved, and their demands for spiritual life have become richer and richer, resulting in higher requirements for cultural tourism. The development of internet technology has brought about the development of new media, and people have shown stronger trust in UGC (User Generated Content). Coupled with the addition of official forces, a series of internet-famous scenic spots have emerged. By analyzing the business models and marketing strategies of internet-famous scenic spots, we can understand market trends, grasp consumer psychology, provide references for marketing activities, and guide scenic spots in shaping their image, enhancing their popularity and influence, thereby attracting the attention of more potential tourists and increasing visitor flow and revenue. In addition, by spreading positive energy and advocating the concept of civilized tourism, we can promote the sustainable development of the tourism industry. Based on Meyrowitz's theory of media space and the analysis of emotional response behavior, this article employs quantitative analysis and comparative analysis methods to elaborate on the shaping of internet-famous scenic spot images by the internet and new media, as well as how emotional marketing in internet-famous scenic spots captures the emotional pain points of tourists to establish emotional connections with them. It is pointed out that building a comprehensive media matrix and enhancing the sense of public participation, experience, and interaction in the marketing process can better establish emotional connections with them.